The Effect of Salary, Motivation, and Works Discipline on Teachers’ Performance - Jerry Chriestanto; Ike Kusdyah Rachmawati; Yunus Handoko (Al-Qalam Institue, 2026)
This study aims to examine the partial and simultaneous effects of salary, motivation, and work discipline on teachers’ performance. A quantitative approach was employed using a saturated sampling technique, involving all 30 teachers in the population. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that partially, salary and motivation do not have a significant effect on teachers’ performance, while work discipline has a significant effect. Simultaneously, salary, motivation, and work discipline have a positive and significant effect on teachers’ performance, with a coefficient of determination of 74%, indicating substantial explanatory power. These findings imply that improving teachers’ performance requires a holistic strategy. Although maintaining a fair and transparent salary system remains important, greater emphasis should be placed on strengthening value-based work discipline and enhancing intrinsic motivation through non-monetary development programs. Such an integrated approach can support sustainable performance improvement in educational institutions.